Pengaruh Turnover Intention Dan Lingkungan Kerja Terhadap Produktivitas Kerja Pegawai Di Kantor Camat Palibelo - Safriani Saf; Rahmatia Rahmatia; Firmansyah Kusumayadi (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to determine and analyze the effect of turnover intention and work environment on employee productivity at the Palibelo District Office. Turnover intention refers to employees’ desire to leave the organization, while the work environment includes both physical and non-physical conditions that affect employee comfort and performance. This research employs a quantitative approach using a survey method. Data were collected through questionnaires distributed to 41 active employees at the Palibelo District Office. The analysis technique used is multiple linear regression with the help of SPSS software. The results show that turnover intention has a negative and significant effect on work productivity, meaning that the higher the employee's intention to leave the job, the lower their productivity. Conversely, the work environment has a positive and significant effect on productivity. A good work environment can enhance employee morale, comfort, and work efficiency. Simultaneously, turnover intention and work environment significantly affect employee productivity. These findings highlight the importance of management's role in creating a conducive work environment and reducing turnover intention to maintain and enhance employee productivity. This research contributes to policy makers in regional government to better consider internal factors that influence employee performance.